Ice hockey research group - Pearsall, D. J. (2007)
The primary purpose of the ice hockey science research group is to evaluate the mechanical function of skates, sticks and protective equipment with respect to skill performance and safety. Several monitoring devices are used to evaluate the mechanical function of skates, sticks and protective equipment with respect to skill performance and safety. Within our research environment we utilize devices such as piezoresistive pressure sensors, electrogoniometers, force plates, accelerometers, high speed video cameras, and three dimensional motion capture devices.Piezoresistive sensors are capable of measuring pressures of up to 100 psi. Using a remote data logger we can collect data from up to 32 of these sensors to map various anatomical features of the body such as points of the foot while inside a ice hockey skate. Electrogoniometers allow for realtime measurement of joint angles in two dimensions. At the ankle for example, we can measure the extent of dorsi and plantar flexion as well as inversion and eversion simultaneously from a single sensor. This data can be uploaded to a computer for later analysis and visualization.